Public response to the rare earth industries in Malaysia - Hassan, Azman; Tengku Ismail , Tengku Hanidza; Saari, Mohd Yusof; Abu Samah, Mohd Armi (Elsevier, 2015)
This paper provides a detailed analysis of public response to the rare earth industry in Malaysia. House-to-house interview was conducted in 2013 (N=1097). Males were more acceptable of the RE industry compared to female (p<0.05) and the government workers were less acceptable of the risk (p<.0.05). Only 7.02% of the respondents reported that they will not accept the RE industry. The principle component analysis on 11 risk perception attributes identified three factors: Risk, Benefit, No government confidence and newness. Multiple regression analysis indicated that public acceptance of the RE industry could significantly be predicted by the ‘Risk’ and ‘Benefit’ factors.